Local Higher Derivations: Tayebeh Lal Shateri - Team, Support (Thai Journal of Mathematics, 2012)
In this paper, we study local higher derivations on some algebras generated by their idempotents. We prove that the space of all bounded higher derivations from these algebras into a unital algebra is reflexive.